2010
DOI: 10.1038/clpt.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Inhaled GLP-1 (MKC253): Proof-of-Concept Studies in Healthy Normal Volunteers and in Patients With Type 2 Diabetes

Abstract: MKC253 is glucagon-like peptide 1 (GLP-1, 7-36 amide) adsorbed onto Technosphere microparticles for oral inhalation. The pharmacokinetics of inhaled GLP-1 and the pharmacokinetic-pharmacodynamic (PK-PD) relationship between inhaled GLP-1 and insulin were analyzed in two trials, one in healthy normal volunteers and the other in patients with type 2 diabetes. Inhaled GLP-1 was absorbed quickly, with peak concentrations occurring within 5 min, and levels returned to baseline within 30 min. Inhaled GLP-1 appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…MannKind is developing an inhalable formulation of native GLP-1 adsorbed to their patented Technosphere microparticles. This drug recently completed a phase Ia clinical trial in which it showed dose-dependent, GLP-1-induced insulin release within six minutes of inhalation in healthy adult males[152]. …”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%
“…MannKind is developing an inhalable formulation of native GLP-1 adsorbed to their patented Technosphere microparticles. This drug recently completed a phase Ia clinical trial in which it showed dose-dependent, GLP-1-induced insulin release within six minutes of inhalation in healthy adult males[152]. …”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%
“…1 These characteristics enable oral inhalation of therapeutics for a wide range of disease states, 1 providing an alternative delivery route for agents currently dosed only by injection, and by making it possible to bypass hepatic first-pass metabolism by absorption directly into the arterial circulation. 2,3 This technology can accommodate therapeutics over a wide molecular size range 1 and has been used to administer insulin and glucagon-like peptide-1 by the pulmonary route in clinical studies. 3,4 A number of other agents, including oxyntomodulin and peptide YY, have been administered in nonclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This technology can accommodate therapeutics over a wide molecular size range 1 and has been used to administer insulin and glucagon-like peptide-1 by the pulmonary route in clinical studies. 3,4 A number of other agents, including oxyntomodulin and peptide YY, have been administered in nonclinical studies. 5 Therapeutics administered via the Technosphere technology demonstrate rapid absorption, believed to be associated with rapid dissolution of the microparticles rather than any FDKP-mediated absorption enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…A MM da amilopectina pode atingir milhões de Dalton. O uso de microesferas baseadas em amido foi sugerido para embolização [51] , administração parenteral e administração nasal [52] de diferentes princípios ativos.…”
Section: Amidounclassified